Special Training Program, Assessement of Hydration and Nutritional Status of Paragliding Athletes in Central Java - Nur Amin; Indri Mulyasari; Arif Wicaksono; Dwi Miya Mustika Said (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Paragliding is one of the extreme sports categories. Several factors that can affect paragliding athletes' achievements include physical fitness, ability to read wind direction, nutritional needs, and fluid needs. The methods used in this training are mentoring, creating special exercise programs, measuring and calculating nutritional status, and calculating the hydration status of athletes. Indicators of training success are measured using questionnaires given to athletes in the time before and after training. The results include: increased knowledge of special exercise programs, calculating and measuring nutritional status, and calculating the hydration status of paragliding athletes.